Gifford Lectures: Professor Holmes Rolston giving the lecture Genes, Genesis and God - Gifford Lectures staff, photographer (Colorado State University. Libraries, 1997)
Dr. Rolston giving a lecture in doctoral gown and hood.
Keywords: Colorado State University; university distinguished professor; philosophy professor; Rolston, Holmes, 1932-2025; Gifford Lectures